2004
DOI: 10.1210/en.2003-0817
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Regulation of Antioxidant Response Element-Dependent Gene Expression by Estrogens

Abstract: Understanding estrogen's regulation of phase II detoxification enzymes is important in explaining how estrogen exposure increases the risk of developing certain cancers. Phase II enzymes such as glutathione-S-transferases (GST) and quinone reductase protect against developing chemically induced cancers by metabolizing reactive oxygen species. Phase II enzyme expression is regulated by a cis-acting DNA sequence, the antioxidant response element (ARE). It has previously been reported that several antiestrogens, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 35 publications
4
54
3
1
Order By: Relevance
“…E 2 induced a 440% decrease in QR levels after 4 and 7 months of treatments ( Figure 1b). Although we have not observed E 2 -induced decrease in QR levels in breast epithelial cell lines (Montano et al, 1998), Ansell et al (2004) reported decreased QR expression in the uteri of E 2 -treated mice. Co-treatment with TAM led to an increase in QR levels in E 2 -treated animals, to levels similar to that observed in control (untreated) animals ( Figure 1b).…”
contrasting
confidence: 76%
“…E 2 induced a 440% decrease in QR levels after 4 and 7 months of treatments ( Figure 1b). Although we have not observed E 2 -induced decrease in QR levels in breast epithelial cell lines (Montano et al, 1998), Ansell et al (2004) reported decreased QR expression in the uteri of E 2 -treated mice. Co-treatment with TAM led to an increase in QR levels in E 2 -treated animals, to levels similar to that observed in control (untreated) animals ( Figure 1b).…”
contrasting
confidence: 76%
“…A study on NQO1 levels in the tissue of ovariectomized mice treated with E 2 over 14 days showed high tissue variability but significantly reduced uterine NQO1 (34). The observed enzyme activity was substantiated by immunoassay of NQO1 protein expression by Western blot (Fig.…”
Section: Induction Of Nqo1 In Liver Cellsmentioning
confidence: 81%
“…Nevertheless, one group has reported NQO1 induction by SERMs in MCF-7 cells, stating that HOT induced NQO1 via an ERhdependent pathway (36). Another group has reported NQO1 induction in both ERa-and ERh-transfected cell lines derived from MCF-7 cells by tamoxifen and HOT (34). Thus, we initially studied the MCF-7 cell line stably transfected with ERh, but observed only very weak induction of NQO1 by the X-DMA SERMs raloxifene and HOT (Supplementary data).…”
Section: Induction Of Nqo1in Breast Cancer Cellsmentioning
confidence: 99%
“…This transcription factor gives robust transcriptional activation so any alteration in its activity will readily be detected [22,28]. As shown in Figure 4, Dlk1 was unable to significantly repress transcription mediated by Nrf2, indicating that the ability of Dlk1 to repress Pit-1-induced transcription is specific.…”
Section: Dlk1 Regulates Pit-1-mediated Transcriptional Activationmentioning
confidence: 99%